Design creativity 2010 - Taura, Toshiharu 1954-; Nagai, Yukari (Springer, 2011)
What is "design creativity"? It is impossible to answer this question without considering why human beings can ? and do ? ?design?. Design creativity is instrumental in not only addressing social problems faced across the world,  but also evoking an innate appreciation for beauty and a sense of personal contentment. Design Creativity 2010 comprises advanced research findings on design creativity and perspectives on future directions of design creativity research. The papers included were presented and discussed at the first ICDC (International Conference on Design Creativity), which was held at Kobe, Japan, in 2010. Design Creativity 2010 encourages readers to enhance and expand their activities in the field of design creativity.